2020
DOI: 10.1039/c9sm01002e
|View full text |Cite
|
Sign up to set email alerts
|

Protonation-induced pH increase at the triblock copolymer micelle interface for transient membrane permeability at neutral pH

Abstract: An increase of bulk-to-interface pH-deviation due to partially protonated interface of tri-block polymer micelle makes an acidic membrane interface transiently permeable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…For this, thin lipid films are obtained from organic solutions containing all lipid components. The films are rehydrated with an aqueous calcein buffer, followed by multiple freeze-thaw cycles, [102,105,108,110] and repeated extrusion through polycarbonate membranes with pore sizes of 100 nm, [101,102,[104][105][106]108,109,113] or larger. [110,115] The outer buffer with free dye is exchanged via size exclusion chromatography (SEC) or centrifugation protocols.…”
Section: Calcein Leakage From Artificial Model Vesiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…For this, thin lipid films are obtained from organic solutions containing all lipid components. The films are rehydrated with an aqueous calcein buffer, followed by multiple freeze-thaw cycles, [102,105,108,110] and repeated extrusion through polycarbonate membranes with pore sizes of 100 nm, [101,102,[104][105][106]108,109,113] or larger. [110,115] The outer buffer with free dye is exchanged via size exclusion chromatography (SEC) or centrifugation protocols.…”
Section: Calcein Leakage From Artificial Model Vesiclesmentioning
confidence: 99%
“…[104][105][106]109] By contrast, Sarkar et al used HEPES buffer (4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid) to investigate calcein leakage of triblock copolymer micelles by varying the pH range from 5.8 to 7.6 outside the liposomes. [102] Furthermore, glucose was added to balance the different osmotic pressures inside and outside the liposomes, whereas other studies mostly used NaCl or KCl for compensation. If very high calcein concentrations (>70 mm) are required, also the weak solubility of calcein at low pH values has to be considered which requires the use of basic buffers (e.g., Tris-HCl pH 10) [103] for the hydration of the lipid film.…”
Section: Calcein Leakage From Artificial Model Vesiclesmentioning
confidence: 99%
“…[20] When adding the acid or alkali for switching the wettability of the surface, most of the reagent doesn't work but only this at the interface acts as the inducer for the protonation of charged groups to change the wettability. [21] Auinger et al [22] reported that during electrochemical reactions, the produces or consumes H + or OH − at the solid-liquid interface can cause a significant change in the pH of the interface region. But the current methods of directly creating acidic or alkaline conditions need further exploration.…”
Section: Introductionmentioning
confidence: 99%